2017
DOI: 10.1016/j.copsyc.2016.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Acknowledging the elephant in the room: how stressful environmental contexts shape relationship dynamics

Abstract: Compared to affluent marriages, lower income marriages develop within a context filled with negative stressors that may prove quite toxic for marital stability. The current paper argues that stressful contexts may undermine marital well-being through two routes. First, external stressors create additional problems within the marriage by diverting time and attention away from activities that promote intimacy between partners. Second, external stress may render spouses ill-equipped to cope with this increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
184
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 151 publications
(200 citation statements)
references
References 36 publications
12
184
1
3
Order By: Relevance
“…The finding that economic strain was negatively related to positive emotions and support in couples suggests the importance of addressing not only negative aspects but also positive individual and dyadic factors within the context of working with couples under stress. Considering that both negative and positive emotions are influenced by stressful contexts (Neff & Karney, ) and they have distinct effects on relationship outcomes (Yee et al, ), we support the view of Huppert and Whittington () that psychological therapies should focus not only on negative well‐being and decreasing the negative psychological symptoms but also on positive well‐being and increasing the experience of positive emotions. A specific intervention, designed for couples experiencing economic strain, is the programme TOGETHER (Falconier, ), which focuses on improving partners' individual resources (such as individual coping and problem‐solving strategies) and dyadic skills (such as communication and SDC).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The finding that economic strain was negatively related to positive emotions and support in couples suggests the importance of addressing not only negative aspects but also positive individual and dyadic factors within the context of working with couples under stress. Considering that both negative and positive emotions are influenced by stressful contexts (Neff & Karney, ) and they have distinct effects on relationship outcomes (Yee et al, ), we support the view of Huppert and Whittington () that psychological therapies should focus not only on negative well‐being and decreasing the negative psychological symptoms but also on positive well‐being and increasing the experience of positive emotions. A specific intervention, designed for couples experiencing economic strain, is the programme TOGETHER (Falconier, ), which focuses on improving partners' individual resources (such as individual coping and problem‐solving strategies) and dyadic skills (such as communication and SDC).…”
Section: Discussionsupporting
confidence: 83%
“…Vinokur et al () showed that depressive symptoms of a partner confronting financial strain dampened the support provided to their unemployed spouse. According to the model proposed by Neff and Karney (), we may assume that economic stress diverts spouses' resources from being connected with their partners to outside stressors, being thus unable to provide emotional and operational support in couples. Shah, Mullainathan, and Shafir () revealed in a series of experiments that economic strain consumes people's attentional resources; a focus on financial difficulties (such as daily basic expenses) will determine them to neglect other important problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, stroking touch increases well-being [Uvn€ as-Moberg, 2004], reduces anxiety [Field et al, 1996] and pain [Coan et al, 2006], and has beneficial effects on multiple stresssensitive systems [Holt-Lunstad et al, 2008]. These antistress effects may promote relationship stability [Neff and Karney, 2017]. Furthermore, touch in romantic couples enhances positive affect in the partner and improves psychological intimacy [Debrot et al, 2013].…”
Section: Figurementioning
confidence: 99%
“…Berscheid (, p.265) stated “Some fragile relationships survive forever because they never encounter a relationship‐toxic environment and some very strong relationships dissolve because fate, or the partners’ ignorance of the vulnerability of their relationships to external forces, …put their relationships in harm's way,” which highlighted the role of contexts in strengthening or deteriorating interpersonal relationships. Neff and Karney () depicted two major routes through which stressful environmental contexts undermine marital relationship: First, stressors outside of marriage deplete resources and energy for pleasurable activities that nourish the relationship; and second, though effective communication and problem‐solving tactics are particularly important for couples under stress, those residing in stressful environments encounter difficulties exhibiting constructive behaviors and positive responses to marital problems. Neighborhood disorder external to the marital relationship would impose a certain level of daily stress on residents, and this would adversely affect the quality of daily interactions with their spouse (Randall & Bodenmann, ).…”
Section: Introductionmentioning
confidence: 99%